Analisis Penyerapan Tenaga Kerja Terdidik Sektor Industri Pengolahan di Pulau Jawa Tahun 2011-2019 - Ahdiyaty Rahmi A. Suaib; Neli Agustina (Seminar Nasional Official Statistics, 2022)
The manufacturing sector as the leading sector provides the largest contribution to GDP in Indonesia. The Java economic corridor is focused on encouraging national industry because Java Island is an industrial center for Indonesia which is expected to be able to absorb a large number of workers so that it can overcome unemployment. However, in reality, the unemployment rate in Java is still relatively high compared to other islands and nationally. In addition, unemployment in Java is still dominated by educated unemployed, so the absorption of labor, especially educated workers, is not optimal in the manufacturing sector. Therefore, the purpose of this study is to analyze the variables that affect the absorption of educated labor in the manufacturing sector in Java Island from 2011-2019. The results of panel regression analysis with Fixed Effect Model (FEM) show that GRDP and investment in the manufacturing sector have a positive and significant effect, UMR has a negative and significant effect. In contrast, the number of industrial business units does not affect the absorption of educated workers in the manufacturing industry. The conclusion is that GRDP and investment have an effect on increasing the absorption of an educated workforce, so it is hoped that the results of this study can be the basis for consideration for policies to increase industrial output and facilitate investment flows so as to optimize the absorption of educated workers.